UPAYA PENINGKATAN PERAN SATRESKRIM DALAM PENYIDIKAN TINDAK PIDANA CURANMOR DI WILAYAH HUKUM POLRESTA SURAKARTA - NAUFAL KURNIA RAHMAN RAHMAN (Police Studies Review, 2022)
ABSTRACT EFFORTS TO INCREASE THE ROLE OF THE POLICE CRIMINAL RESERSE UNIT IN MOTOR VEHICLES THEFT INVESTIGATION TO INCREASE CRIME CLEARANCE IN THE JURIDICTION OF THE SURAKARTA POLICE REGION. Naufal Kurnia Rahman, 18.057, naufalkr8@gmail.com The National Police is state institution that has the function of enforce the law. With the many phenomena in society, including vehicles theft problems. This research is motivated by data on increase in the number of crimes (JTP) Surakarta Police, accompanied by decrease in the settlement of criminal acts (PTP) theft of motor vehichles in the last 3 years. To overcome the decrease of crime clearance (PTP), there needs to be efforts of increase the role of the police criminal reserse unit in motor vehicles theft investigation based on Perkap No.6 of 2019 on Criminal Investigation. In this research, the problems include how The Role of Police Criminal Reserse Unit in investigation of motor vehicles theft and how to increase the surakarta of Police criminal reserse unit in the investigation of motor vehicles theft to increase crime clearance in The Surakarta Police jurisdiction. To Process the data, researcher use the theory of management, law enforcement theory, the concept of investigation, and the concept of motor vehicle theft. In this research was conducted with qualitative approach, type of case field research as well as data collection with interviews, observations, and document studies. For the data analysis technique, researcher uses data reduction, data presentation, and drawing conclusion. The results showed that the implementation of investigation in motor vehicles theft by The Police Criminal Reserse Unit has not been optimal. Referring to the theory and concept used,and several efforts from The Surakarta of Police Criminal Reserse. Keywords : The Police Criminal Reserse Unit, Investigation, Motor vehicles theft.